Schistosome tegumental ecto-apyrase (SmATPDase1) degrades exogenous pro-inflammatory and pro-thrombotic nucleotides - Akram A. Da’dara; Rita Bhardwaj; Yasser B.M. Ali; Patrick J. Skelly (PeerJ, 2014)
Schistosomes are parasitic worms that can survive in the hostile environment of the human bloodstream where they appear refractory to both immune elimination and thrombus formation. We hypothesize that parasite migration in the bloodstream can stress the vascular endothelium causing this tissue to release chemicals alerting responsive host cells to the stress. Such chemicals are called damage associated molecular patterns (DAMPs) and among the most potent is the proinflammatory mediator, adenosine triphosphate (ATP). Furthermore, the ATP derivative ADP is a pro-thrombotic molecule that acts as a strong activator of platelets. Schistosomes are reported to possess at their host interactive tegumental surface a series of enzymes that could, like their homologs in mammals, degrade extracellular ATP and ADP. These are alkaline phosphatase (SmAP), phosphodiesterase (SmNPP-5) and ATP diphosphohydrolase (SmATPDase1). In this work we employ RNAi to knock down expression of the genes encoding these enzymes in the intravascular life stages of the parasite. We then compare the abilities of these parasites to degrade exogenously added ATP and ADP. We find that only SmATPDase1-suppressed parasites are significantly impaired in their ability to degrade these nucleotides. Suppression of SmAP or SmNPP-5 does not appreciably affect the worms’ ability to catabolize ATP or ADP. These findings are confirmed by the functional characterization of the enzymatically active, full-length recombinant SmATPDase1 expressed in CHO-S cells. The enzyme is a true apyrase; SmATPDase1 degrades ATP and ADP in a cation dependent manner. Optimal activity is seen at alkaline pH. The Km of SmATPDase1 for ATP is 0.4 ± 0.02 mM and for ADP, 0.252 ± 0.02 mM. The results confirm the role of tegumental SmATPDase1 in the degradation of the exogenous pro-inflammatory and pro-thrombotic nucleotides ATP and ADP by live intravascular stages of the parasite. By degrading host inflammatory signals like ATP, and pro-thrombotic signals like ADP, these parasite enzymes may minimize host immune responses, inhibit blood coagulation and promote schistosome survival.